On Common Fixed Point Theorems in the Stationary Fuzzy Metric Space of the Bounded Closed Sets - Dong Qiu; Chongxia Lu; Wei Zhang; Yuzhong Mo (Abstract and Applied Analysis)
Under the -contraction conditions, we prove common fixed point theorems for self-mappings in the space of the bounded closed sets in the complete stationary fuzzy metric space with the -fuzzy metric for the bounded closed sets.